THE EFFECT OF ZAKAT, INFLATION AND EXPORTS ON NATIONAL ECONOMIC GROWTH WITH THE INTERVENING VARIABLE OF HUMAN DEVELOPMENT INDEX - Cholidah Nur Khasana (RADJA PUBLIKA, 2026)
This study aims to determine the effect of zakat, inflation, and exports on the human development index with national economic growth as an intervening variable in the 2016–2020 period. The research method used is quantitative with saturated sampling technique, involving 60 data for each variable. The research data is in the form of secondary time series data sourced from the National Zakat Agency, Bank Indonesia, and the Central Statistics Agency. The analysis was carried out through descriptive tests, stationarity tests, classical assumption tests, and statistical tests with the help of Eviews 12 software. The results of the study show that: (1) zakat has a positive and significant effect on economic growth; (2) inflation has a negative and significant effect on economic growth; (3) exports have a positive but insignificant effect on economic growth; (4) economic growth has a positive but insignificant effect on the human development index; (5) zakat and inflation affect the human development index through economic growth; (6) exports do not affect the human development index through economic growth.